2016
DOI: 10.1007/s00586-016-4609-y
|View full text |Cite
|
Sign up to set email alerts
|

Do Modic changes have an impact on clinical outcome in lumbar spine surgery? A systematic literature review

Abstract: Preoperative MC showed a trend toward a negative correlation with clinical improvement in patients undergoing discectomy for LDH and a positive correlation with clinical improvement in patients undergoing TDR for degenerative disc disease. However, it is questionable whether the differences surpass the minimal clinically important difference (MCID). In patients undergoing fusion surgery, there was insufficient evidence to draw any conclusions. Future studies should include a larger patient material, focus on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 52 publications
4
44
2
Order By: Relevance
“…Patients with a shorter duration of sick leave, absence of comorbidity, lower ODI score and higher education were more likely to be employed at eight-year follow-up. The positive association between Modic changes and ≥ 15 points improvement in ODI score after TDR in our study should be interpreted in light of the findings in a recent systematic review on the impact of Modic changes on outcome after lumbar spine surgery [29]. This review identified four TDR studies (including the two-year results from the present study [13]).…”
Section: Discussionsupporting
confidence: 66%
“…Patients with a shorter duration of sick leave, absence of comorbidity, lower ODI score and higher education were more likely to be employed at eight-year follow-up. The positive association between Modic changes and ≥ 15 points improvement in ODI score after TDR in our study should be interpreted in light of the findings in a recent systematic review on the impact of Modic changes on outcome after lumbar spine surgery [29]. This review identified four TDR studies (including the two-year results from the present study [13]).…”
Section: Discussionsupporting
confidence: 66%
“…The natural history of modic changes in the lumbar spine is often marked by conversion from one type to another (60). Some studies suggest that fusion increases the conversion of modic changes Type 1 to modic changes Type 2, probably by correcting the mechanical instability, and these changes appear to be a good indicator of satisfactory outcome after fusion surgery (61). Vital et al (62) demonstrated that all Type 1 changes converted into either Type 2 changes or back to normal within 6 months following lumbar fusion, which paralleled clinical improvement in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the extent of MC may be just as important for the clinical outcome as the presence of MC. Our findings should be interpreted in light of the findings in a recent systematic review on the impact of MC on outcome after lumbar spine surgery [304]. This review identified four TDR studies (including the two-year results from the Norwegian TDR study [29]).…”
Section: Exposure Variablesmentioning
confidence: 81%